UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TAPAK DARA (Catharantus roseus) DI DESA LISABATA TERHADAP PERTUMBUHAN BAKTERI S t ap h yl o c oc c u s a u r eu s DENGAN MENGGUNAKAN METODE DIFUSI AGAR - Anatje J. Pattipeilohy; Cut Bidara Panita Umar; Mnhammad Taip Pattilouw (Pusat Riset dan Inovasi Nasional, 2022)
The tapak dara plant is known as an ornamental plant that is efficacious for relieving muscle pain , antidepressant , medicine for various diseases ( ie relieving swelling caused by wasp stings , nosebleeds and sore throats ), antidote , antibacterial , and lowering blood pressure in humans . Purpose of Research of this is to identify the content of the chemical from the leaves of tread virgin ( Catharantus roseus ), which serves as an antibacterial and to test the activity of antibacterial extract ethanol leaves tread virgin ( Catharantus roseus ) against the growth of bacteria Staphylococcus aureus by using the method of diffusion in order. Method which are used in research this is experimental by using the method of diffusion in order. This study used concentrations of 5%, 20%, 60%, and 80%. Positive control (+) chloramphenicol antibiotic , negative control (-) aquadest . Results of the study is the extract of leaves of Tread Dara ( Catharantus roseus ) can inhibit the growth of bacteria in a concentration of 80% by having an average zone of inhibition of which is 21 mm including the category is very strong and the concentration of 60% at 20 mm.